Exposure-Based Therapy for Symptom Preoccupation in Atrial Fibrillation: An Uncontrolled Pilot Study. Issue 6 (November 2017) - Särnholm, Josefin; Skúladóttir, Helga; Rück, Christian; Pedersen, Susanne S.; Braunschweig, Frieder; Ljótsson, Brjánn
Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia. Patients often experience a range of symptoms resulting in a markedly reduced quality of life, and commonly show symptom preoccupation in terms of avoidance and control behaviors. Cognitive behavior therapy (CBT) has been shown to improve symptom burden and quality of life in other somatic disorders, but has never been evaluated in patients with AF. The purpose of this study was to evaluate the potential efficacy and feasibility of an AF-specific CBT protocol in an uncontrolled pilot study. The study included 19 patients with symptomatic paroxysmal (intermittent) atrial fibrillation who were assessed pre- and posttreatment and at 6-month follow-up. The CBT lasted 10 weeks and included exposure to physical sensations similar to AF symptoms, exposure to avoided situations or activities, and behavioral activation. We observed large within-group improvements on the primary outcome AF-specific quality of life measurement AFEQT posttreatment (Cohen's d = 1.54; p < . 001) and at 6-month follow-up ( d = 1.15; p < . 001). We also observed improvements in self-reported frequency and severity of AF symptoms. All participants completed the treatment and treatment satisfaction was high. This study demonstrates the potential efficacy and feasibility of a novel CBT approach to reduce symptoms and increase quality of life in AF patients. Highlights: Symptom preoccupation may maintain disability in atrial fibrillation (AF). We studied cognitive behavioral therapy (CBT) targeting symptom preoccupation in AF. Participants showed reduction in cardiac symptoms and increased quality of life. Participants' satisfaction indicate that CBT is a feasible treatment option.